Farm machines - Wykeham, Nicholas; Scott, Jerry (Milwaukee : Raintree Childrens Books, 1979)
This book describes various pieces of farm machinery and their uses.
Includes index.
osc 04/03/2019
Loans
Keywords: Agricultural machinery; Agricultural machinery; Machinery